PENGARUH AKUNTABILITAS, KETIDAKPASTIAN LINGKUNGAN, DAN KOMITMEN PIMPINAN TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN (STUDI EMPIRIS PADA SKPD KOTA DUMAI) - Wendi Adha; Vince Ratnawati; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Transparency of financial reporting requires organizations to present the financial statements are free of material false and biased information to outside parties. This is consistent with the concept of the reliability of information in the financial statements which should be free of errors and misleading understanding of material, presenting any facts honestly, and can be verified. Transparency can be affected by the financial management accountability, leadership and commitment to environmental uncertainty. The research was carried out in the city with the object of research is Dumai departments, agencies, and offices in Dumai amounting to 33 Workers Local Government Unit. Samples taken in this study amounted to 99 respondents. The data was collected using a questionnaire which was then analyzed using linear regression. The test results showed that leadership accountability and commitment affect the application of the local government financial reporting transparency Dumai, whereas environmental uncertainty does not affect the application of the transparency of financial pelaporang. The magnitude of the effect of accountability, environmental uncertainty and leadership commitment to the implementation of the local government financial reporting transparency Dumai is 77%.Keywords: Accountability, Environmental Uncertainty, Leadership Commitment and Application Transparency of Financial Reporting